Managed Care In Healthcare Insurance: A Case Study In Indonesia For Review - Kartika Destya Arini; Imas Nurhasanah; Mohammad Amnurokhim Malahade; Erlina Puspitaloka Mahadewi (International Journal of Health and Pharmaceutical (IJHP), 2025)
The process of goods and services procurement within the government environment still has vulnerabilities to fraud, which necessitates proper handling. This study aims to identify the factors that can influence efforts to prevent fraud in the procurement of goods and services using an e-procurement system. The data for this research was obtained through the distribution of questionnaires to employees at the Procurement Services Unit (ULP) and the Regional Financial and Asset Management Agency (BPKAD) Office of Dompu Regency. The sampling method used in this study is purposive sampling. Furthermore, the research data were tested using multiple regression analysis. This study demonstrates that the variables of technology utilization, e-procurement, internal control systems, organizational culture, employee ethics, and religiosity can influence the prevention of fraud in the procurement of goods and services. The research findings can serve as a reference for evaluating the use of information technology through e-procurement and the application of internal control systems for optimal results. Additionally, it is important to consider human resources, specifically employees, in maintaining organizational culture, good ethics, and religious values as a foundation for actions in the workplace to avoid various deviant or unlawful behaviors.